Analisis Laju Fouling pada Tube Heat Exchanger 53 EA-1001 - Yasir Amani; M. Ilham Maulana (Jurnal Teknik Mesin Unsyiah, 2016)
Appliance of Heat Exchanger type 53 EA-1001 exist in company PT. Pupuk Iskandar Muda operate the time some long time is hence formed by coat of fouling, existence of fouling will lessen the hot coefesien transfer totally (U) to a point appliance planning reach the minimum price, this information is obtained to can to schedule for the periodic routine of sweeping as well as commutation of pipe of appliance of heat exchange which is improper used again by prediction is maximum gather fouling at appliance of Heat Exchanger. Existence of fouling will lessen the final hot coeffesient transfer to a point planning, so that can be scheduled for by a routine treatment. Hot influence Coeffesient transfer totally ( U) to fluid flow speed, resulting height of stream speed. 8640 hour operate for at fouling factor 0,0082 (Rd) yield the volume fouling 0,0066 m3 need the treatment of age Heat Exchanger 27th year of gagging fouling at volume 63,585 m3. Stream emiting a stream is laminar with the value 950 Btu.ft3 / hr.lb.s energy and 1,46 times from missing energy in the situation without there is fouling.